Investigation of structures in the Alabanda Bouleuterion by electrical resistivity method - Karavul, Can; Karaaslan, Hasan; Demirkol, Askin (Arabian journal of geosciences, 2016)
The workspace as Bouleuterion (parliament house) is located in the ancient city of Alabanda far approximately 7 km from Aydin, Çine. The works on the city plan are still continued by the Department of Archeology in Adnan Menderes University. In this work, a geophysical study based on electrical resistivity tomography (ERT) approach is used to bring out the existence of the buried structures and situations of ruins in Bouleuterion. This study is a good example of implementation of the electrical resistivity method to the archeology in a specific area (Bouleuterion). Furthermore, the paper shows to researchers practically advantages and disadvantages of Wenner and dipole-dipole arrays that widely used in archeological prospection. Also with this work, a Bouleuterion has been subject of a geophysical article for the first time. By archeology and geophysics evaluations, it is proved that these ruins such as the cavea, stage, orchestra, and entrances are parts of the Bouleuterion.